Real‐Time Mimicking the Electronic Structure of N‐Coordinated Ni Single Atoms: NiS‐Enabled Electrochemical Reduction of CO2 to CO (Adv. Energy Mater. 35/2022). Issue 35 (15th September 2022) - Han, Man Ho; Kim, Dongjin; Kim, Sangkuk; Yu, Seung‐Ho; Won, Da Hye; Min, Byoung Koun; Chae, Keun Hwa; Lee, Woong Hee; Oh, Hyung‐Suk
Abstract : CO2 Reduction Reaction In article number 2201843, Woong Hee Lee, Hyung‐Suk Oh, and co‐workers report that NiS nanoparticles mimicking Ni–NC in real‐time, enhance the CO2 reduction reaction activity in a zero‐gap electrolyzer. Just as Ni‐NC was developed by mimicking the enzymes, NiS also mimics the electronic structure of Ni–NC under operating conditions. The cathodic potential and alkaline media in the device are thought to allow for the real‐time electronic structure of the NiS catalyst to mimic that of the NiNC based catalyst.